2021
DOI: 10.35940/ijitee.a9585.1111121
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Building with Basements Under Seismic Excitation Considering Soil Structure Interaction

Abstract: In modern construction, there is a trend to go deeper below the grade level in terms of basements which can be utilized for parking, shopping malls or a combination of both. In such cases, dynamic soil properties have a significant effect of activating dynamic soil structure interaction phenomenon during earthquake. Here in present study an effort is made to study the behavior of a building by varying five and three number of basements considering dynamic soil structure interaction. Issues like influence zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this context, the base of a structure is the level at which the lateral displacement is zero [3]. This issue has been the subject of a lot of theoretical analysis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the base of a structure is the level at which the lateral displacement is zero [3]. This issue has been the subject of a lot of theoretical analysis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…They compared the responses, base shear, story drift, axial forces, and periods of vibration, for buildings with and without basement walls. Authors in [4] studied the effect of basements on the structure behavior by carrying out seismic analysis of a 3D model of a 12-story RC building with 4 basements using SAP200. They carried out static, modal, and time history analysis, and concluded that base shear, bending moment and acceleration were reduced, whereas time period and displacement were increased.…”
Section: Introductionmentioning
confidence: 99%